Shallow defects levels and extract detrapped charges to stabilize highly efficient and hysteresis-free perovskite photovoltaic devices. (May 2020) - Liu, Xixia; Cheng, Yuanhang; Tang, Baoshan; Yu, Zhi Gen; Li, Mengsha; Lin, Fen; Zhang, Siwen; Zhang, Yong-Wei; Ouyang, Jianyong; Gong, Hao
Abstract: Perovskite materials are promising candidates for efficient optoelectronic applications. However, the highly ionic nature of perovskite crystals would induce the defects formation within perovskite during device operation, which is detrimental to the device performance and long-term stability. Herein, a strategy to decrease the defects levels and prompt the extraction of detrapped chargers in perovskite films is realized by introducing an ultra-thin 2D WS2 interlayer to guide van der Waal quasi-epitaxial perovskite growth. Various optoelectronic characterizations and DFT calculation clearly reveal that the 2D WS2 inhibits the native defects formation and shallow the deep defects levels within perovskite. In addition, the 2D WS2 interlayer can promptly extract the detrapped charges to reduce the interfacial recombination. Consequently, the among-highest efficiency of 20.92% with significantly enhanced Voc and FF and decent moisture stability (90% over 20 days) is achieved for the inverted planar perovskite solar cell. This work enlightens the deep understanding of highly efficient and stable perovskite photovoltaic devices with the aid of 2D materials, which should contribute to the development of devices based on perovskite/2D heterojunction. Graphical abstract: Image 1 Highlights: 2D WS2 /3D perovskite heterojunction is fabricated for 20.92% inverted planar perovskite solar cell. 2D WS2  can help the perovskite photovoltaic devices keep long-term stability. 2D WS2  can guide epitaxial growth of the perovskite to improve its crystallinity, crystal size and film uniformity. 2D WS2  can improve defects formation energy and shallow defects levels within perovskite. 2D WS2  possesses ultra-high hole mobility to extract the detrapped charges within perovskite.